Increased Plasma Levels of Mitochondrial DNA and Normal Inflammasome Gene Expression in Monocytes Characterize Patients With Septic Shock Due to Multidrug Resistant Bacteria - Busani, Stefano; De Biasi, Sara; Nasi, Milena; Paolini, Annamaria; Venturelli, Sophie; Tosi, Martina; Girardis, Massimo; Cossarizza, Andrea (Frontiers in Immunology, 2020)
Introduction. The activity and regulation of inflammasome is receiving increasing attention in septic shock. Moreover, there is a growing body of evidence suggesting that mitochondrial DNA (mtDNA) can play a role as biomarker of disease severity and even mortality both in adults and children in critically ill setting. However, no data are available on the amount of circulating mtDNA and inflammasome gene expression in multi-drug resistant (MDR) bacteria septic shock. For this reason, the aim of this study was to determine whether plasma mtDNA levels and inflammasome gene expression in monocytes could be related to severity in patients admitted to intensive care unit (ICU) with septic shock due to MDR pathogens. Materials and Methods. Peripheral blood mononuclear cells (PBMC) and plasma were isolated from up to 20 ml of venous blood by density gradient centrifugation in patients admitted to ICU with the diagnosis of septic shock due to MDR-bacteria. Then, CD14+ monocytes were sorted, and RNA and DNA were extracted. NLRP3, PYCARD, AIM2 and NAIP expression level was analysed by RT-PCR. Plasma circulating mtDNA levels were quantified by digital droplet PCR. Basal and outcome characteristics of the patients were collected. Age-matched healthy subjects were chosen as controls. Results. 19 patients with septic shock and 20 healthy subjects were enrolled in the study. A small trend toward an increased expression of inflammasome genes was observed in septic shock patients, who also displayed a marked tendency to an increased expression of IL-18 and IL-1ß genes. Circulating mtDNA levels were significantly higher in septic shock patients if compared to healthy subjects, and patients who died in ICU were characterized by higher level of mtDNA if compared to those who were dismissed after 7 days of ICU. No correlations were found between mtDNA and inflammasome level and other clinical variables. Conclusions. Despite many limitations, our data suggest that in patients with septic shock caused by MDR pathogens the expression of main inflammasome genes was comparable to that of healthy patients without infection. Furthermore, our data evidence a possible role of mtDNA as a prognostic marker of severity in septic shock from MDR.